Paulista: A networked translocal sonic performance between São Paulo and Belfast. Issue 2 (1st December 2012) - Hickmann, Felipe; Chaves, Rui
First performed in June 2011, Paulista used fixed and mobile streaming technology to create a translocal, musical and sonic performance linking SARC (Belfast/Northern Ireland), LAMI (São Paulo/Brazil) and Paulista Avenue, in the heart of São Paulo's city centre. By discussing the performative and compositional strategies employed in this work, we aim at highlighting the central role played by the network in articulating notions of liveness and dramaturgy, as well as fostering new ideas and processes to engage dislocated spaces in shared musical practice.